2004
DOI: 10.1128/mcb.24.10.4207-4220.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Sox-2 Regulatory Regions Display Their Activities in Two Distinct Types of Multipotent Stem Cells

Abstract: The Sox-2 gene is expressed in embryonic stem (ES) cells and neural stem cells. Two transcription enhancer regions, Sox-2 regulatory region 1 (SRR1) and SRR2, were described previously based on their activities in ES cells. Here, we demonstrate that these regulatory regions also exert their activities in neural stem cells. Moreover, our data reveal that, as in ES cells, both SRR1 and SRR2 show their activities rather specifically in multipotent neural stem or progenitor cells but cease to function in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 58 publications
3
102
1
1
Order By: Relevance
“…Our results indicate that it is precisely this upstream distal enhancer that is activated in mammospheres, as a luciferase reporter with this enhancer is strongly induced upon sphere formation. The upstream enhancer was strongly activated in undifferentiated embryonic stem cells and its activity was lost upon differentiation (Tomioka et al, 2002), it is the same behaviour as observed in multipotent neural stem cells (Miyagi et al, 2004;Miyagi et al, 2006). In embryonic stem cells, a non-consensus octamer-binding site in the enhancer is occupied by Oct3/4-Sox2 dimers, however, as we did not observe Oct4 expression in mammospheres, a different mechanism must operate.…”
Section: Sox2 Activation In Breast Cancer Stem Cellssupporting
confidence: 78%
“…Our results indicate that it is precisely this upstream distal enhancer that is activated in mammospheres, as a luciferase reporter with this enhancer is strongly induced upon sphere formation. The upstream enhancer was strongly activated in undifferentiated embryonic stem cells and its activity was lost upon differentiation (Tomioka et al, 2002), it is the same behaviour as observed in multipotent neural stem cells (Miyagi et al, 2004;Miyagi et al, 2006). In embryonic stem cells, a non-consensus octamer-binding site in the enhancer is occupied by Oct3/4-Sox2 dimers, however, as we did not observe Oct4 expression in mammospheres, a different mechanism must operate.…”
Section: Sox2 Activation In Breast Cancer Stem Cellssupporting
confidence: 78%
“…Such mechanisms possibly include modulatory effects at promoter and/or enhancer regions of various transcription factors. For example, two distinct Sox2 enhancers are active in multipotent neural progenitors but cease to function in differentiated cells (Zappone et al, 2000;Miyagi et al, 2004). The mouse Pax6 gene has three promoters under the control of at least six different enhancers, directing Pax6 expression in distinct tissues (reviewed by Morgan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect immunocytochemistry was carried out as previously described [26] with cells that had been cultured on coverslips coated with poly-D-lysine and laminin. For 5-Bromo-2 0 -deoxyuridine (BrdU) labeling experiments, cells were treated with 10 lg/ml BrdU for 30 minutes.…”
Section: Immunocytochemistrymentioning
confidence: 99%